The Analysis of Stock Price of Primary Consumer Goods Sector Companies on the Indonesia Stock Exchange - Pratiwi, Maharani; Marlina (Garuda Prestasi Nusantara Consulting, 2022)
This study aims to analyze the effect of Liquidity, Activity, Profitability and Exchange Rate on Stock Prices of Companies in the Primary Consumer Goods Sector on the Indonesia Stock Exchange. The population in this study are primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sampling technique used is probability sampling with the slovin technique, obtained 53 companies and the research period is 5 years, in order to obtain 265 research data. The data analysis technique uses panel data regression analysis with Eviews 12 and a significance level of 5%. In the study, explaining the results, namely Liquidity with the Current Ratio (CR) proxy has no effect on stock prices, Activity with the Total Asset Turnover (TATO) proxy has no effect on stock prices, Profitability with Return on Equity (ROE) proxies has a positive effect on stock prices, Value exchange with proxies The middle rate has a negative effect on stock prices. Keywords: Stock Price; Liquidity; Activity; Profitability; Exchange rate